The extinction time under mutational meltdown driven by high mutation rates. Issue 7 (6th July 2022) - Lansch‐Justen, Lucy; Cusseddu, Davide; Schmitz, Mark A.; Bank, Claudia
Abstract: Mutational meltdown describes an eco‐evolutionary process in which the accumulation of deleterious mutations causes a fitness decline that eventually leads to the extinction of a population. Possible applications of this concept include medical treatment of RNA virus infections based on mutagenic drugs that increase the mutation rate of the pathogen. To determine the usefulness and expected success of such an antiviral treatment, estimates of the expected time to mutational meltdown are necessary. Here, we compute the extinction time of a population under high mutation rates, using both analytical approaches and stochastic simulations. Extinction is the result of three consecutive processes: (a) initial accumulation of deleterious mutations due to the increased mutation pressure; (b) consecutive loss of the fittest haplotype due to Muller's ratchet; (c) rapid population decline toward extinction. We find accurate analytical results for the mean extinction time, which show that the deleterious mutation rate has the strongest effect on the extinction time. We confirm that intermediate‐sized deleterious selection coefficients minimize the extinction time. Finally, our simulations show that the variation in extinction time, given a set of parameters, is surprisingly small. Abstract : Mutational meltdown is an eco‐evolutionary process in which the accumulation of deleterious mutations causes the extinction of a population. This process is the basis for successful medical treatment of RNA virus infections with mutagenic drugs. We compute the extinction time under mutational meltdown in a high‐mutation‐rate regime, which is an important measure to determine the usefulness and expected success of such an antiviral treatment.